LXX-Isaiah as translation and interpretation : the strategies of the translator of the Septuagint of Isaiah - Troxel, Ronald L., 1951- (Supplements to the Journal for the Study of Judaism, 2008)
This book offers a fresh understanding of how Isaiah was translated into Greek, by considering the impact of the translator's Alexandrian milieu on his work. Whereas most studies over the past fifty years have regarded the book's free translation style as betraying the translator's conviction that Isaiah's oracles were being fulfilled in his day, this study argues that he was primarily interested in offering his Greek-speaking co-religionists a cohesive representation of Isaiah's ideas. Comparison of the translator's interpretative tacks with those employed by the grammatikoi in their study of Homer offers a convincing picture of his work as an Alexandrian Jew and clarifies how this translation should be assessed in reconstructing early textual forms of Hebrew Isaiah.